2020
DOI: 10.3390/su12166437
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Key Insights of Sociological Risk Theory into the Ecosystem Services Framework

Abstract: Environmental risks give urgency to the need to understand the society–nature relationship. While the ecosystem services (ES) framework allows analysis of interrelationships between biophysical supply and human demand for natural resources, further research is needed to understand what drives societal demand for ES. Here, I explore how incorporation of the key sociological theories of risk (systems theory, ‘world risk society’, and cultural theory of risk) can advance this understanding. By examining these the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…The integration of sociological cultural theory of risk represents a new approach in ES research that may enlighten how ES priorities and demand are shaped by cultural worldviews (Peter, 2020). In this study, a closer look at the identified cultural types provides valuable information about what motivates ES prioritisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of sociological cultural theory of risk represents a new approach in ES research that may enlighten how ES priorities and demand are shaped by cultural worldviews (Peter, 2020). In this study, a closer look at the identified cultural types provides valuable information about what motivates ES prioritisation.…”
Section: Discussionmentioning
confidence: 99%
“…The cultural theory of risk assumes that our perceptions of nature and society, and the risks associated with these perspectives, are socioculturally constructed (Renn, 2008). We extended this assumption to propose that the theories' 'grid-group typology' (Thompson et al, 1990) can be used as a conceptual framework to understand how stakeholders' cultural worldviews drive ES priorities and demand (Peter, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This literature focuses mainly on social vulnerability, resilience and adaptation (SVRA) [6]. We must pay attention to the risk to society [7,8], documented in relation to the environment since the end of the last century [9,10]. This is known as the "mitigation" stage [11].…”
Section: The Social Context and Adaptive Management For Biodiversity ...mentioning
confidence: 99%
“…As noted by Himes-Cornell et al [74], valuations of ecosystem services generally focus on "what the value of an ecosystem service is", leaving what people actually value about that service in the background. In this context, sociology and its theoretical input can help to understand how socio-cultural worldviews held by stakeholders influence ES priorities and demands [75]. In this line, there are several sociological theories that have been studied in the context of ES, for the consideration of intangible dimensions such as, for example, the "social theory and Bourdieu's concept of habitus", which seeks to understand the process by which relational values are socially constructed and shared [76].…”
Section: Sociology's Contribution To the Assessment Of Ecosystem Serv...mentioning
confidence: 99%